Anti-inflammatory Effect of Thymus kotschyanus Boiss. & Hohen. Extract on Rat's Hind Paw Edema Induced by Carrageenan - A Bakhtiarian; F Aarabi Moghaddam; MM Zamani; SG Ghamami; B Farahanikia; M Khanavi (Institue of Medicinal Plants, ACECR, 2011)
Background: Advantages of herbal drugs have been known to human being for many years and they have been used for treatment of many diseases. Nowadays, inflammation is known to be one of the basic pathologic causes of the diseases. Objective: In this study the anti-inflammatory effect of Thymus kotschyanus Boiss & Hohen was investigated. Methods: Forty two Wistar rats were used in three divided groups. In the first group, extract of Thymus kotschyanus Boiss & Hohen in doses of 50, 100, 150, 200 mg/kg was injected intra peritoneal and after one hour they were treated with hind paw edema test with carrageenan. In the second group, Indomethacin with the dose of 5 mg/kg was injected one hour before carrageenan and in the third one, saline was injected before carrageenan, every hours after carrageenan injection to rat's right hind paw the inflammation was separately measured by the change in the volume of mercury (plethysmometer). Results: Indomethacin and Thymus kotschyanus Boiss & Hohen extract had significantly reduced edema in all five measurements (p<0.001). There was no significant difference between Indometacin and the extract in reducing edema in the first to fourth hour, but in the fifth hour, the herbal drug showed a significant difference of anti-inflammatory effect with Indometacin in all doses (p<0.05). Conclusion: The methanolic extract of Thymus kotschyanus Boiss & Hohen has anti- inflammatory effect in all doses which is dose dependant and can be used instead of or as a synergist for Indometacin. Higher doses of herbal extract may have more anti-inflammatory effects.